2017
DOI: 10.1103/physrevmaterials.1.074407
|View full text |Cite
|
Sign up to set email alerts
|

Chemical solution synthesis and ferromagnetic resonance of epitaxial thin films of yttrium iron garnet

Abstract: We report the fabrication of epitaxial Y 3 Fe 5 O 12 (YIG) thin films on Gd 3 Ga 5 O 12 (111) using a chemical solution method. Cubic YIG is a ferrimagnetic material at room temperature, with excellent magneto-optical properties, high electrical resistivity, and a very narrow ferromagnetic resonance, which makes it particularly suitable for applications in filters and resonators at microwave frequencies. But these properties depend on the precise stoichiometry and distribution of Fe 3+ ions among the octahedra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The synthesis of epitaxial thin-films (≈15 nm) of YIG was also recently reported by PAD. 116 The slow growth of the films in quasi-equilibrium conditions produce an excellent chemical, crystalline and magnetic homogeneity. As a result, a narrow ferromagnetic resonance (long spin relaxation time), has been reported in YIG grown by PAD.…”
Section: Thermodynamic Stabilization Of Complex Oxidesmentioning
confidence: 99%
“…The synthesis of epitaxial thin-films (≈15 nm) of YIG was also recently reported by PAD. 116 The slow growth of the films in quasi-equilibrium conditions produce an excellent chemical, crystalline and magnetic homogeneity. As a result, a narrow ferromagnetic resonance (long spin relaxation time), has been reported in YIG grown by PAD.…”
Section: Thermodynamic Stabilization Of Complex Oxidesmentioning
confidence: 99%
“…(ii) Magnetron sputtered YIG usually yields wider FMR linewidths, and inhomogeneous line broadening is frequently observed [37][38][39][40]. (iii) For large-scale, low-cost chemical solution techniques, such as spin coating, strongly broadened FMR linewidths and increased Gilbert damping parameters were reported [41,42]. (iv) Liquid phase epitaxy (LPE) from high-temperature solutions (flux melts), is a wellestablished technique.…”
Section: Introductionmentioning
confidence: 99%
“…As a chemical solution route, PAD provides an attractive opportunity to grow films close to thermodynamic equilibrium conditions. The characteristic growth conditions of PAD have already been shown to be advantageous for the stabilization of materials with complex structures or chemical composition, such as misfit cobalt oxides 29 and Y 3 Fe 5 O 12 yttrium iron garnet 30 . On the other hand, PAD might also be useful to clarify the role of structural strain in stimulating spontaneous cationic ordering because it has been shown that structural strain accommodation may proceed in a different way in samples prepared by PAD.…”
Section: Introductionmentioning
confidence: 99%